BAHASA DAKWAH STRUKTURAL DAN KULTURAL DA’I DALAM PERSPEKTIF DRAMATURGI - Farhan Farhan (JURNAL AT-TURAS, 2014)
More and more thrive linguic a society, then language of propaganda should more and more fleksibel and dynamic that easy be understood. Therefore, preachers intelligent will read in deep and detail to needs object preaching, It is good while be in structural position or cultural. Through metodologi kualitatif, this write will try describe about language of propaganda structural-cultural preachers in perspective Dramaturgi. Through study character preachers da’i -Habib Hadi Zainal Abidin al Habsyi in Probolinggo City east Java, this research conclude that language propaganda Habib Hadi bin Muhammad al Habsyi in the field political organic and society organic be delivered in verbal and non verbal. The message of verbal with language-language propaganda form word that good (qoulun ma’rufun) and form word that correct (qoulon sadidun). While the message non verbal be delivered in nonverbal visual form the message proksemic and the message kinesic. While propaganda that do through field art, social culture through language verbal with word that cool and soft (Qoulun Layyinun) and word that correct (Qoulun Sadidun) and word that good (Qoulun Ma’rufun).